2016
DOI: 10.4172/pharmaceutical-sciences.1000146
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Bonding Modes between Two Antidiabetic Drugs with beta-Glucosidases from Different Species

Abstract: Qi, et al.: Analysis of Bonding Modes between Antidiabetic Drugs with β-Glucosidases β-glucosidase is one of the critical enzymes to the type 2 diabetes, which belongs to a large family of glycoside hydrolases. In this article, we attempted to explore the binding modes between two drugs and β-glucosidases by comparing their bonding modes with β-glucosidases from different species. Results showed that the binding orientations and geometrical conformation of synthetic drug (miglitol) and natural product (quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Molecular docking analysis was used to demarcate the activity of the tested compounds against digestive enzymes. Previous studies reported that phenolic compounds and flavonoids were able to bind to the pockets of α -amylase, β -glucosidase and pancreatic lipase, forming enzyme-inhibitors complexes [ 20 , 21 , 22 ]. Furthermore, the researchers evaluated the potential antidiabetic activity of the flowering whole plant AEEE in diabetic rats in order to assess its antidiabetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking analysis was used to demarcate the activity of the tested compounds against digestive enzymes. Previous studies reported that phenolic compounds and flavonoids were able to bind to the pockets of α -amylase, β -glucosidase and pancreatic lipase, forming enzyme-inhibitors complexes [ 20 , 21 , 22 ]. Furthermore, the researchers evaluated the potential antidiabetic activity of the flowering whole plant AEEE in diabetic rats in order to assess its antidiabetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Homology modeling was proposed by using the crystal structure of S.cerevisiae isomaltase as the template [34,35]. By using PROCHECK, the final structure of α-glucosidase generated from homology modeling was evaluated and suggested reliable results [36,37]. It can be seen from the Ramachandran plot that 87.5% of residues of the final 3D structure lay in most favored regions (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study found that quercetin xed in the binding pocket of β-glucosidase mainly through hydrogen bonds and hydrophobic interactions between the complexes. The residues involved in H-bonds were mainly polar amino acids, such as Trp442, Gln57 and Asn426 [30]. The molecular docking illustrated that MGGG bind strongly to β-glucosidase catalytic site with an energy binding of -8.98 kcal/mol.…”
Section: Modeling Of Mggg Binding Mode Against α-Amylasementioning
confidence: 98%